The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.4319/lo.2007.52.6.2325
|View full text |Cite
|
Sign up to set email alerts
|

Bioturbation changes the patterns of benthic emergence in zooplankton

Abstract: We investigated the effects of two functionally different deposit feeders, the amphipod Monoporeia affinis and the bivalve Macoma balthica, on the benthic emergence of copepods (Acartia spp., Eurytemora affinis, Temora longicornis), cladocerans (Bosmina longispina maritima, Daphnia spp.), and rotifers (Synchaeta spp., Keratella spp., Notholca spp.) in the northern Baltic Sea. We performed 3.5-week laboratory experiments in June-July and in September-October using surface sediment containing zooplankton eggs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…2, see S4 for details). Phosphorus recycling seems to have been less affected by faunal activity than nitrogen recycling, in line with results from other studies (Marinelli and Williams, 2003;Viitasalo et al, 2007;Norkko et al, 2013). This is likely in part explained by the strong dependence of phosphorus a Water concentrations not measured; % for these treatments were estimated using water concentration data from the nearest available treatment multiplied by the ratio in nominal amounts.…”
Section: Effects On Benthic Communities and Benthic-pelagic Couplingmentioning
confidence: 50%
See 1 more Smart Citation
“…2, see S4 for details). Phosphorus recycling seems to have been less affected by faunal activity than nitrogen recycling, in line with results from other studies (Marinelli and Williams, 2003;Viitasalo et al, 2007;Norkko et al, 2013). This is likely in part explained by the strong dependence of phosphorus a Water concentrations not measured; % for these treatments were estimated using water concentration data from the nearest available treatment multiplied by the ratio in nominal amounts.…”
Section: Effects On Benthic Communities and Benthic-pelagic Couplingmentioning
confidence: 50%
“…In our experiment, indirect effects were mediated by the benthic community. Although sediment mixing by M. balthica may promote copepod benthic emergence, high predation on calanoid eggs (Viitasalo et al, 2007) reduces egg availability considerably. The shallow water depth in the mesocosm may have allowed sinking of copepod eggs throughout the experiment, which by T231 encountered favourable conditions (i.e.…”
Section: Effects On Pelagic Systemmentioning
confidence: 99%
“…Similarly, Stå hl-Delbanco and Hansson (2002) found that an active bioturbator (an isopod) had a larger positive effect on the recruitment of freshwater cyanobacteria than a less active one (an arthropod larva). Furthermore, Viitasalo et al (2007) found that resuspension by M. affinis may enhance the hatching of zooplankton eggs in surface sediment, but that predation on eggs cancels this positive effect at high amphipod densities.…”
Section: Discussionmentioning
confidence: 95%
“…While near the sediment surface, these resting eggs remain vulnerable to predators, but at least some can survive passage through a gut. Bioturbation, sometimes including ingestion, brings buried resting eggs to the surface for further development (Marcus and Schmidt‐Gengenbach ; Viitasalo et al ). In contrast, benthic embryos of most marine animals do not undergo prolonged arrested development and do not survive ingestion, sulfide, or prolonged anoxia, although embryos of some benthic harpacticoid copepods tolerate sulfide as well as anoxia (Vopel et al ) and the horseshoe crab Limulus buries clutches of embryos that can tolerate days of hypoxia (Palumbi and Johnson ).…”
Section: Discussionmentioning
confidence: 99%